A Case of Primary Intraosseous Adenoid Cystic Carcinoma of the Mandible - Erika Sasaki; Kenji Yamagata; Takayuki Hagiwara; Ryo Takasaki; Satoshi Fukuzawa; Fumihiko Uchida; Naomi Ishibashi-Kanno; Hiroki Bukawa (Hindawi Limited, 2023)
Primary intraosseous adenoid cystic carcinoma (PIACC) of the jaw is rare. To our knowledge, only 51 cases have been reported in the English literature. We present a rare case of PIACC arising in the mandible with multiple bone metastases and review the previous articles. A 70-year-old woman presented with paresthesia of the right chin and lower gingiva for 4 months. Radiography revealed an irregular radiolucent region on the right side of the ramus, infiltrating to the mandibular canal. Biopsy revealed a pathological diagnosis of adenoid cystic carcinoma. Multiple bone metastases were present in the sternum, scapula, and thighs. The treatment effect was progressive disease for chemotherapy; therefore, best supportive care was provided for 3 years.